Wild reindeer Rangifer tarandus (L.) in Chukotka - Chernyavskii, Felix B.; Kretchmar, Mikhail A. (Rangifer, 1998)
We reviewed historical records of the abundance and distribution of wild reindeer {Rangifer tarandus L.) in Chukotka and studied reindeer numbers, distribution and behavior from 1983 to 1993. There were large numbers of wild reindeer in Chukotka until the end of the eighteenth century, but during the nineteenth century the population declined probably from intensive harvest after the introduction of firearms by the Cossacks. During the nineteenth century herding of domestic reindeer also increased, and reindeer herders continued to hunt wild reindeer intensively. During the 1950s there were only about 8500 wild reindeer in two separate herds in Chukotka. By the late 1970s the wild reindeer population had increased to about 11 000. Ten years later we estimated 16 534 reindeer, and found only one contiguous population. Presently, the population calves and spends the summer in the Anadyr Uplands and migrates west and southwest to spend the winter in forest tundra and northern taiga regions. Predators, primarily wolves and brown bears, kill a significant number of calves. Today, the wild reindeer in Chukotka coexist with 300 000 domestic reindeer. However, current costs of gasoline and helicopters make it prohibitive to herd reindeer in much of central Chukotka, so that wild reindeer have room for expansion. Poaching is a major conservation problem. Poachers shoot wild reindeer from helicopters to obtain velvet antlers. Leaders of domestic reindeer cooperatives encourage poaching by telling people that wild reindeer are in fact just stray domestic reindeer and there is no enforcement of game laws.